(untitled) (Research, Society and Development, 2022)
The consumption of a hypercaloric diet leads to an increase in obesity, which can lead to an inflammatory state. Thus, the objective of this work was to analyze the influence of this inflammation on the behavior of obese animals. For this, male Swiss mice were kept under controlled feeding were divided into 2 groups; Group Cafeteria diet, which received high calorie foods and standard chow for rodent, while the control group received only standard rat chow. After 30 days, 2 hours before the behavioral tests, both groups were subdivided, so that half of the animals of each group received LPS by intraperitoneal injection (100 g/kg; i.p.) and the other half received saline injection ( 0.9% NaCl, 100g/kg; i.p.) (Groups: Cafeteria Diet + LPS and Cafeteria Diet + Saline; Normal Diet + LPS and Normal Diet + Saline). Afterwards, they were submitted to the Open Field Test and the Forced Swim Test and later euthanized for collection and weighing of the epididymal and retroperitoneal adipose tissue. There was an increase in weight, epididymal and retroperitoneal fat in mice treated with cafeteria diet compared to normal diet. LPS had a more pronounced effect in the cafeteria diet group, with a decrease in the number of entries in the periphery and in the center, in addition to the total number of entries and rearing, in the open field test. There was also an increase in time floating in the forced swim test. Therefore, the accumulation of body fat, by the ingestion of a hypercaloric diet, potentiates the inflammatory state caused by LPS, leading to an anxiogenic effect.